Effect of timing cord clamping on a vaginally delivered infant of a primigravida in terms of the incidence of hyperbilirubinemia - Maria Magdalena Setyaningsih; Wisoedhanie Widi Anugrahanti (Akademi Keperawatan Dharma Husada Kediri, 2015)
Delayed cord clamping leads to the increased level of haematocrite and victocytes which is high risk of hyperbilirubinemia . This study is to determine if there is an effect of timing of cord clamping relating to the incidence of hyperbilirubinemia on newborn, and to create formulating the standard procedures in maternal interventions related to the timing of cord clamping, another objective is preventing interventions of its occurrence when the clamping is performed immediately after birth. Crossectional study was applied design of the research. Population and samples included infants spontaneus by healthy primigravidas.Two trials were included, 20 participants of each received interventions of cord clamping more than equalivalent 1 minute and less than 1 minute followed by bilirubin assessment 48 hours after birth, and analysed by using Linier Regression. There is no significant effect of timing of cord clamping on newborn with regard to hiperbilirubinemia, because the effect of the clamping on bilirubin level reaches up to 68.2%, while the other 31.8% of the varying levels are affected by other factors. There is a need to conduct other relevant studies aimed to prevent hyperbilirubinemia starting from antenatal to postnatal stage. Key Words: Jaundice, Newborn, Hyperbilirubinemia, Time of Clamping, Primigravidas